Manual orgánico y funcional y manual de clasificación, valoración de puestos y reglamento de selección de personal para la empresa pública de vialidad Zamora Chinchipe "Vialzachin" e.p., del cantón Zamora, provincia de Zamora Chinchipe, para el año 2015 - Jumbo Quezada, Adriana Narcisa (2016)
The work is done by the need to improve the current performance of the company VIALZACHIN EP, which seeks to provide better performance and attention to the road system of Zamora Chinchipe, hence the importance of making the thesis topic entitled " MANUAL MANUAL ORGANIC AND FUNCTIONAL CLASSIFICATION, VALUATION OF POSTS AND RECRUITMENT RULES FOR ROAD PUBLIC COMPANY Zamora Chinchipe "VIALZACHIN" EP, CANTON Zamora, Zamora Chinchipe province, by the year 2015 ", the work carried out Organic determines that the current manual is not according to the number of staff and processes running in the company. The interest develops in research is given to developing the organic functional manual so as to allow the process-based work, as well as proper control of, human talent that works in the company. Among developed objectives is the development of the new organizational structure of the company which is designed according to the guidelines established for the public service, thereby defining line of authority will be maintained in the development of activities. The second objective seeks to establish the minimum activities for each of the tasks set for the Public Enterprise Roads Zamora Chinchipe, VIALZACHIN EP Run road maintenance activities. The third objective seeks to establish the location lines to facilitate the work in the order and priorities so that information flows from operating level to the level of administrative decision. The fourth objective led to the development manual classification and valuation of positions by setting the correct way to make based recruitment through recruitment rules that will be applied to all types of contract.